Drama Segitiga Karpman untuk Meningkatkan Kesadaran Diri Siswa terhadap Perilaku Bullying - Bashirudin Debipriamuda; Dany M Handarini; M Ramli (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2019)
Bullying is one of the events that repeatedly arises in schools and associated to varies between individuals. One of the sources of bullying is the poor self-awareness held by students. Self-awareness is one of the students skill must acquire. However, in reality there are still many students who have poor self-awareness. This study tries to investigate the effectiveness of the Karpman Drama Triangle to build up students self-awareness using Quasi Experiment Design. The research subjects consisted of 15 junior high school students who had poor self-awareness. The results of the study indicated that the Karpman Drama Triangle was useful in enhancing students self-awareness to reduce bullying behavior. It also informs us that the Karpman Drama Triangle can be an option to develop students self-awareness in reducing conflicts and bullying behavior that exists between students. The difference in the status of self-awareness between students before and after treatment is expressed is also illustrated. The Karpman Drama Triangle can be an alternative solution for handling and facilitating students who have poor social interaction and growing conflict situations towards peacefully.